1999
DOI: 10.1200/jco.1999.17.7.2092
|View full text |Cite
|
Sign up to set email alerts
|

Role of Radiation Therapy in the Combined-Modality Treatment of Patients With Extensive Disease Small-Cell Lung Cancer: A Randomized Study

Abstract: The addition of ACC HFX RT to the treatment of the most favorable subset of patients led to improved survival over that obtained with CHT alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
221
0
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(241 citation statements)
references
References 21 publications
12
221
0
8
Order By: Relevance
“…We found that radiotherapy was associated with improved survival, which is consistent with previous studies. In a randomized trial, the combination of chemotherapy and thoracic radiotherapy compared with chemotherapy alone resulted in a median 5-year survival rate of 9.1% versus 3.7%, respectively, for patients with ES-SCLC (Jeremic et al, 1999). In another randomized study, prophylactic cranial irradiation reduced the risk of symptomatic brain metastases and also improved survival in patients with ES-SCLC (Slotman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We found that radiotherapy was associated with improved survival, which is consistent with previous studies. In a randomized trial, the combination of chemotherapy and thoracic radiotherapy compared with chemotherapy alone resulted in a median 5-year survival rate of 9.1% versus 3.7%, respectively, for patients with ES-SCLC (Jeremic et al, 1999). In another randomized study, prophylactic cranial irradiation reduced the risk of symptomatic brain metastases and also improved survival in patients with ES-SCLC (Slotman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The use of TRT in patients with a CR at distant sites gave rise to significant improvement of survival. Median survival was 17 months for patients who received TRT, compared to only 11 months for those who received chemotherapy alone (Jeremic et al, 1999). The 5-year survival rate was 9.1% for the TRT group and was 3.7% for the chemotherapy-only group (P = 0.041) (Jeremic et al, 1999).…”
Section: Role Of Radiotherapy In the Treatment Of Ed-sclcmentioning
confidence: 97%
“…Median survival was 17 months for patients who received TRT, compared to only 11 months for those who received chemotherapy alone (Jeremic et al, 1999). The 5-year survival rate was 9.1% for the TRT group and was 3.7% for the chemotherapy-only group (P = 0.041) (Jeremic et al, 1999). However, this one small-, single-center randomized study has not led to the routine use of TRT in ED-SCLC.…”
Section: Role Of Radiotherapy In the Treatment Of Ed-sclcmentioning
confidence: 99%
See 2 more Smart Citations